Pomak Villages in Izmir “What language do you dream in?” - Sepetcioğlu, Tuncay Ercan (Academician Publishing Book DOI Portal, 2023)
This book focuses on the Pomak villages located in the rural areas of Izmir. Pomaks are a Muslim community living in the eastern Balkans along the Rhodope Mountains and the Danube River, speaking a Slavic dialect. This community mostly resides in Bulgaria, but has lost and dispersed a significant portion of its population until a century ago. Starting from the late 19th century, particularly due to the pressures from Bulgarian and Russian administrations and non-indigenous Christian populations, Pomaks began to migrate to safer places, primarily Anatolia. Izmir and its surroundings are one of the final destinations of this migration. In a period where research on Pomaks in Turkey mostly focuses on their ethnic origins, this book examines the settlement history and characteristics of isolated Pomak villages in the highland areas of Izmir. Documents from the Ottoman Archives are combined with oral history and observations in the region. This study specifically focuses on Pomak villages in the Bayındır and Kemalpaşa districts, where Pomak migrants are culturally distinct from the local population and other migrant communities. It investigates a migration and settlement process that started in the Balkans and ended in these villages, using documents from the Ottoman Archives and field research data. This study aims to answer questions such as: Who are the Pomaks? Which settlements in the rural areas of Izmir host Pomak migrants who have a distinct culture from the local population and other migrant communities, especially in terms of their mother tongue? What political or military events served as the final homes for the migrants before they continued their journeys? When and how were these communities established; how were the villages founded? Who are the original inhabitants? What are the population and settlement characteristics? How do the migrant communities in the Pomak region differ from others? Do Pomak communities have similar socio-economic and cultural characteristics?